analisis pengendalian internal pada prosedur pemberian kredit investasi (studi pada PT. Bank Tabungan Negara Cabang KKupang) - Elis Seubelan; Herly M. Oematan (Universitas Nusa Cendana, 2021)
This study aims to find out how the procedures for granting investment credit is and how to internal control the procedure for granting investment credit at PT. State Savings Bank Tbk Kupang Branch. The research approach used in this research is descriptive qualitative. The type of data used in this study is qualitative data, the data source used in this research is primary data, the data collection technique used is by conducting interviews with informants. The results showed that (1) PT. Bank Tabungan Negara Tbk Kupang Branch has carried out the procedure for granting investment credit in accordance with the procedure, starting from the socialization of credit from the authorities, followed by the submission of documents to meet the requirements, after that a credit analysis was carried out to determine the credibility of the debtor and finally the debtor was waiting for disbursement. on the credit application. (2) PT. The State Savings Bank Tbk Kupang Branch has carried out internal control on the procedure for granting investment credit properly in accordance with the five components of internal control, namely the control environment, risk assessment, control activities, information and communication and monitoring.